2010
DOI: 10.1161/circresaha.110.233080
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Modulates Expression and Processing of Amyloid Precursor Protein

Abstract: Rationale:The exact etiology of sporadic Alzheimer disease (AD) is unclear, but it is interesting that several cardiovascular risk factors are associated with higher incidence of AD. The link between these risk factors and AD has yet to be identified; however, a common feature is endothelial dysfunction, specifically, decreased bioavailability of nitric oxide (NO).Objective: To determine the relationship between endothelial derived NO and the expression and processing of amyloid precursor protein (APP). Key Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 18 publications
10
171
0
Order By: Relevance
“…A recent evidence indicates that NO may protect against increase in Aβ through decreasing the levels of APP and APP-cleaving enzyme, β-secretase. 25 The observed increase of the levels of soluble Aβ in AD&HT mice might, therefore, result from the upregulation of APP and β-secretase, consecutive to the reduction of NO production in the brain. Moreover, Aβ42 levels may be regulated by angiotensin-converting enzyme which has been shown to cleave Aβ42 at several sites, including the resulting formation of Aβ40.…”
Section: Discussionmentioning
confidence: 99%
“…A recent evidence indicates that NO may protect against increase in Aβ through decreasing the levels of APP and APP-cleaving enzyme, β-secretase. 25 The observed increase of the levels of soluble Aβ in AD&HT mice might, therefore, result from the upregulation of APP and β-secretase, consecutive to the reduction of NO production in the brain. Moreover, Aβ42 levels may be regulated by angiotensin-converting enzyme which has been shown to cleave Aβ42 at several sites, including the resulting formation of Aβ40.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study reported that mouse microvascular cells in cultures express BACE1. 21 To examine whether BACE1 was present in human cerebral vessels in vivo, especially in the cerebral vessels from CAA, a double-labeling immunohistochemical technique was performed in the brains with CAA. We found BACE1 expression in human cortical vessels identified with 2 vessel markers: a-SM actin and collagen IV (figure 1B).…”
Section: Bace1 Is Expressed In Cerebral Vascular Cellsmentioning
confidence: 99%
“…With advancing age, endothelial dysfunction primarily results from reduced nitric oxide (NO) bioavailability (Taddei et al 2001). Not only is NO the key dilator produced by the endothelium (Vanhoutte 2003), but endothelial-derived NO can also decrease the expression of amyloid precursor proteins (Austin et al 2010), the accumulation of which is a characteristic feature of Alzheimer's disease (O'Brien and Wong 2011). Reactive oxygen species, particularly superoxide, reduce NO bioavailability and oxidative stress has been implicated as a major factor leading to impaired EDD with aging (Taddei et al 2001).…”
Section: Introductionmentioning
confidence: 99%